2021
DOI: 10.1371/journal.pone.0258506
|View full text |Cite
|
Sign up to set email alerts
|

Genetic effect on free amino acid contents of egg yolk and albumen using five different chicken genotypes under floor rearing system

Abstract: Chicken eggs play an important role as food resources in the world. Although genetic effects on yolk and albumen contents have been reported, the number of chicken genotypes analyzed so far is still limited. To investigate the effect of genetic background on 10 egg traits, 19 yolk amino acid traits, and 19 albumen amino acid traits, we evaluated a total of 58 eggs from five genotypes: two Japanese indigenous breeds (Ukokkei and Nagoya) and three hybrids (Araucana cross, Kurohisui, and Boris Brown) under a floo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 39 publications
1
8
0
1
Order By: Relevance
“…Our study showed that the most abundant amino acids in the albumen of the eggs were aspartic acid, serine, glutamic acid, valine, leucine, and lysine, while histidine was the most limiting amino acid. These results are in agreement with other reports, where the same amino acids were in the abundance, irrespective of the source of eggs [ 6 ]. The Gln supplementation to laying hens in the present study resulted in an increase in asparagine, proline, phenylalanine, tyrosine, and tryptophan content.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our study showed that the most abundant amino acids in the albumen of the eggs were aspartic acid, serine, glutamic acid, valine, leucine, and lysine, while histidine was the most limiting amino acid. These results are in agreement with other reports, where the same amino acids were in the abundance, irrespective of the source of eggs [ 6 ]. The Gln supplementation to laying hens in the present study resulted in an increase in asparagine, proline, phenylalanine, tyrosine, and tryptophan content.…”
Section: Discussionsupporting
confidence: 94%
“…More frequently the consumers’ preference relating pro-health properties, e.g., antioxidants, lipid content, have been taken into consideration [ 42 ]. However, in the past few years the relationship between eggs amino acids and taste (sweetness, sourness, saltiness, bitterness, and umami) has been studied [ 6 ]. Among these amino acids are essential and non-essential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the AAA aspartic acid, lysine, methionine, and tyrosine were considered the main contributor to the antioxidant properties of eggs, from which RF2 had the highest cumulated value compared with RF0. Cysteine, methionine, tyrosine, and histidine were reported as being relatively easily oxidized [ 37 ], however, the antioxidant potential of rosehip meal, improves their antioxidant properties to prevent protein oxidation. The EAA/TAA ratio, cysteine/SAA ratio, as well as total SAA, were significantly higher in RF1 and RF2, compared with RF0 eggs, showing high variability for the determined AA.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, single nucleotide polymorphism of fatty acid desaturase1 could enhance egg flavor intensity and continuity, while negatively correlated with n-6/n-3 ratios [34]. Similarly, free amino acid profiles of Araucana eggs were significantly varied in egg flavor as compared to Ukokkei, Nagoya, Kurohisui, and Boris Brown egg flavors [35]. The hardboiled egg flavor differences could be attributed to variations in dry matter contents of eggs in laying hens [36].…”
Section: Sensory Characteristics Of Hardboiled and Scrambled Eggs Of ...mentioning
confidence: 99%